Validation of genital appearance satisfaction scale and the cosmetic procedure screening scale for women seeking labiaplasty. (March 2013) - Veale, David; Eshkevari, Ertimiss; Ellison, Nell; Cardozo, Linda; Robinson, Dudley; Kavouni, Angelica
Abstract: Background : Existing outcome studies on women seeking labiaplasty have not used a validated scale that is specific for satisfaction with genital appearance. They have also not screened for the presence of body dysmorphic disorder (BDD). There are therefore two primary aims of this study (1) to validate the Genital Appearance Satisfaction (GAS) scale in women seeking labiaplasty and (2) to modify and validate a version of the Cosmetic Procedures Screening questionnaire (COPS-L), which has previously been used to screen for BDD. Method : Two groups of women were recruited: a group desiring labiaplasty and a control group. All participants completed the GAS, the COPS-L and other general measures of mood, disgust sensitivity, sexual satisfaction and body image quality of life. Results : Both the GAS and COPS-L demonstrated good internal consistency, concurrent and convergent validity with measures of related constructs, and discriminated between women seeking labiaplasty and controls. Three factors were identified in the GAS but were not robust enough to recommend their use clinically as subscales. The COPS-L discriminated between women seeking labiaplasty with and without BDD. Discussion : We recommend that both the GAS and the COPS-L be routinely used for audit and outcome monitoring of interventions for women distressed by the appearance or function of their genitalia. The GAS has an advantage in assessing additional functional symptoms in such women. The COPS-L may be helpful in identifying women with BDD.